Classification and Methodology of National Movement Games Training Physical Qualitie - Nurullaev Abdukhamid Ruzimbaevich; M.A.Ruzimbaev (Research Parks Publishers, 2021)
The article discusses the types of national action games that nurture physical qualities and each type of game that nurtures physical qualities.